2009
DOI: 10.3357/asem.2599.2009
|View full text |Cite
|
Sign up to set email alerts
|

Acute Otitic Barotrauma During Hypobaric Chamber Training: Prevalence And Prevention

Abstract: The prevalence of barotitis after hypobaric chamber training is low in our study, suggesting that a pre-chamber medical check including clinical examination and tympanometry could be effective in identifying subjects at risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 6 publications
0
2
0
1
Order By: Relevance
“…Prevalence estimations vary significantly. The lowest numbers, 1.5 -2.4%, have been reported in pressure chamber measurements of Italian military personnel 16,20 , while a prevalence of 4.1% has been reported in Japanese pilots 23 . In contrast, 37.6 -55.5% of Danish commercial pilots have reported at least one ME barotrauma during their career 5,25 and in other publications, 41.0 -84.0% of airline passengers have reported similar symptoms 18,30 .…”
Section: Introductionmentioning
confidence: 85%
“…Prevalence estimations vary significantly. The lowest numbers, 1.5 -2.4%, have been reported in pressure chamber measurements of Italian military personnel 16,20 , while a prevalence of 4.1% has been reported in Japanese pilots 23 . In contrast, 37.6 -55.5% of Danish commercial pilots have reported at least one ME barotrauma during their career 5,25 and in other publications, 41.0 -84.0% of airline passengers have reported similar symptoms 18,30 .…”
Section: Introductionmentioning
confidence: 85%
“…Therefore, to assert that an ETD is present and to evaluate the probability of barotitis during flight, the dynamic function of ET patency should be tested with specific tests during simulated flights as in a pressure chamber [22,23]. A study of 335 military pilots carried out to evaluate the Eustachian Tube functionality in hypobaric chamber has shown that some of them had barotitis even if their otoscopical evaluation and tympanogram were normal [24]. This situation could be related to a very slight obstruction of the tube lumen due to focal inflammation not detectable by either otoscopy or tympanometry.…”
Section: Discussionmentioning
confidence: 99%
“…Sporadic or prolonged exposure to these agents can damage the health of workers. One of the most common health problems associated with the aviation profession is middle-ear barotrauma, defined as inflammation of the tympanic membrane and middleear cavity due to differences in pressure between the cavity and external atmospheric pressure, a phenomenon also associated with diving or hyperbaric oxygen therapy [2,3].…”
Section: Introductionmentioning
confidence: 99%